UJI AKTIVITAS ANTIDIABETES KOMBINASI EKSTRAK ETANOL DAUN ALPUKAT DAN RIMPANG TEMULAWAK PADA TIKUS DM TIPE-2 YANG MENGALAMI RESISTENSI INSULIN - Mamik Dwi Anggraini; Yance Anas; Sumantri Sumantri (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Avocado’s leaves and Curcuma xanthorrizarhizoma contain compounds of flavonoids, alcaloids,triterpenoids and curcumin, where the compounds are effective as antidiabetic agents. This study aims to prove the effect of antidiabetic combination of extracts on insulin resistence type-2 diabetic rats then to compare it with a single extract. This research used pre-test and post-test control group design. The 30 test animals were divided into two treatment groups. Five control groups of rats were they given 1,25 mL aquabides/KgBW/day, and 25 rats were divided into five groups and given were given 1,8 IU insulin/KgBW/day for 14 days. Group I was control of 12,5 mL CMC-Na/KgBW/day 0,5%, group II was positive control of 150 mg metformin/KgBW/day, group III was avocado’s leaves extract, group IV was extract of Curcuma xanthorriza rhizoma, and group V was combination extract. The extracts of group III-V were given the same dose, that was given 200 mg/KgBW/day for 14 days. The meansurement of antidiabetic effect was done by comparing the GDP value of rats before and after treatment. The GDP concentrations of rats were analyzed using T-paired testand Wilxocon test, whereas the comparative data of percentage GDP decrease was tested using Kruskall Wallis test then followed by Mann-Whitney test. The results showed that the effect of antidiabetic combination of extract in insulin resistence type-2 diabetic rats as the percentage GDP decrease was 22.03%. The effect of decreasing GDP concentration at the ratio of 1:1 extract did not differ significantly with the single extract of 200 mg Curcuma xanthorrizarhizoma/KgBW/day. Keywords: Avocado’s leaves, Curcuma xanthorriza rhizoma, Antidiabetic effect test, Comparison combination of both extracts with single extract.